منظومة المسكوممباني ودورها في الدراسات الفلكية بإندونيسيا (JOURNAL OF INDONESIAN ISLAM, 2011)
KH Muhammad Faqih bin Abdul Jabbar, a Muslim scholar  from Maskumambang, Dukun, Gresik, East Java, wrote a phenomenal manuscript called Al-Manzumah al-Daliyah fi Awa’il al-Ashhur al-Qamariyah about the science of astronomy. The manuscript was discovered in Pondok Pesantren Langitan, then digitalled by Islamic manuscripts of Pesantren (MIPES) with code Lang 05. This work is in the form of 48 stanza poems. The formula number in the Abjadiyah letters which is divided into ones, tens, hundreds and thousands is referred to within the work. Faqih combines one letter with another so that a formula for determining “basithah” year and “kabisat” year in the Arabic calendar. He develops an argument that with the count formula is also known how to determine the initial month of Ramadan. Astronomy (Falak) Science is written using the traditional formula that is very valuable. Along with the development of science and technology, the science of astronomy is now using a modern formula that’s more easily and accurately, but the traditional cosmography it has a great share in the emergence of modern astronomy. This Manzumah deserves further review for academic development.